2015
DOI: 10.4049/jimmunol.1401451
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Ubiquitin-Specific Protease 4 Promotes Th17 Cell Function under Inflammation by Deubiquitinating and Stabilizing RORγt

Abstract: RORγt is a key transcription factor that controls the development and function of inflammatory Th17. The mechanisms that regulate RORγt stability remain unclear. We report that Th17 cells highly express the deubiquitinase ubiquitin-specific protease (USP)4, which is essential for maintaining RORγt and Th17 cell function. Inhibition of the catalytic activity of USP4 with vialinin A, a compound derived from Chinese traditional medicine, dampened Th17 differentiation. USP4 interacted and deubiquitinated K48-linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 20 publications
3
72
0
Order By: Relevance
“…5d). Ubiquitylation of FOXP3, RORγt and T-bet controls transcription factor stability, and dysregulation of the ubiquitylating or de-ubiquitylating enzymes can induce phenotypic plasticity in these cells [183][184][185] . Blocking the activity of sirtuin 1 preserves FOXP3 acetylation, enhancing FOXP3 stability and T Reg cell function 186,187 , whereas inhibition of sirtuin 1 increases RORγt acety lation in T H 17 cells, which impedes RORγt activity 188 , thus creating another therapeutically exploitable dichotomy between inflammatory and regulatory cells.…”
Section: Gene Expression Regulationmentioning
confidence: 99%
“…5d). Ubiquitylation of FOXP3, RORγt and T-bet controls transcription factor stability, and dysregulation of the ubiquitylating or de-ubiquitylating enzymes can induce phenotypic plasticity in these cells [183][184][185] . Blocking the activity of sirtuin 1 preserves FOXP3 acetylation, enhancing FOXP3 stability and T Reg cell function 186,187 , whereas inhibition of sirtuin 1 increases RORγt acety lation in T H 17 cells, which impedes RORγt activity 188 , thus creating another therapeutically exploitable dichotomy between inflammatory and regulatory cells.…”
Section: Gene Expression Regulationmentioning
confidence: 99%
“…Reports have suggested a role for ubiquitination in the regulation of RORγt stability (3437). However, in our studies, RORγt WT and the K446R mutant expressed at similar levels (Fig.3A, 3F and 3G).…”
Section: Resultsmentioning
confidence: 99%
“…Less is known about the mechanisms of post-transcriptional regulation that is responsible for regulating RORγt function. Reports that RORγt stability is regulated by ubiquitination-mediated degradation mechanisms (3437) suggested a role for ubiquitination in RORγt-mediated differentiation. In this study, we identified RORγt K446 as a ubiquitination site that limits Th17 differentiation by interfering with the recruitment of co-activator SRC1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, USP4 deubiquitylates Ro52 in transformed cell lines 72 and thus limits the expression of cytokines needed for Th17 generation 69 . Second, it directly interacts with RORγT in primary human Th17 cells and deubiquitylates RORγT in transformed cell lines 73 . USP17 (also known as DUB-3) is a second DUB that maintains RORγT stability 74 .…”
Section: Th17 Cellsmentioning
confidence: 99%